Analytical modeling of thermo-mechanical stress for bond wire of IGBT module - Dai, Xingyu; Yang, Xin; Wu, Xinlong; Tu, Chunming; Liu, Guoyou (Microelectronics and reliability, 2021)
Reliability of bond wires in power modules has been a main subject of interest in both industry and academia. Until now, analytical modeling of thermo-mechanical stress mainly focuses on the loop height variation of bond wires instead of plastic strain, which is the key factor causing the fatigue failure. In this paper, an analytical model for analyzing plastic strain of bond wires in IGBT modules is proposed. Using a laser displacement sensor, the dynamic loop height variations of bond wires under different heating currents are experimentally measured, based on which the finite element analysis (FEA) simulation is calibrated and verified to reveal the actual thermo-mechanical stress. In this way, the usefulness of our proposed method is verified by comparing its simulation results with those from the multi-physics fields FEA method. Finally, the relationship between the bonding angle and the plastic strain at the heel of bond wires is established. This study would provide new perspectives into further research on thermo-mechanical fatigue analysis and optimal design of bond wires in power modules. •An analytical model for analyzing plastic strain of bond wires in IGBT modules is proposed.•The FEA simulation is calibrated based on the experimental results of loop top displacement.•The relationship between the bonding angle and the plastic strain at the heel of bond wires is established.•The models have been compared with FEA simulation results with good agreements.